Role of an Electrical Potential in the Coupling of Metabolic Energy to Active Transport by Membrane Vesicles of Escherichia coli - Hirata, Hajime (1973)
Membrane vesicles from E. coli can oxidize D-lactate and other substrates and couple respiration to the active transport of sugars and amino acids. The present experiments bear on the nature of the link between respiration and transport. Respiring vesicles were found to accumulate dibenzyldimethylammonium ion, a synthetic lipid-soluble cation that serves as an indicator of an electrical potential. The results suggest that oxidation of D-lactate generates a membrane potential, vesicle interior negative, of the order of -100 mV. In vesicles lacking substrate, an electrical potential was created by induction of electrogenic efflux of K(+) with the aid of the K(+) ionophores, valinomycin and monactin. These conditions induced transient accumulation by the vesicles of [(14)C]proline and other metabolites. Experiments with inhibitors and ionophores indicate that neither ATP nor the respiratory chain is involved; the electrical potential generated by K(+) efflux is coupled directly to the transport systems. The results verify two predictions derived from Mitchell's chemiosmotic hypothesis: respiring vesicles generate an electrical potential of the proper polarity and magnitude; and a membrane potential is in itself sufficient to drive the active transport of amino acids and other metabolites.